WEBSTER'S Third new International Dictionary of English Language unabridged with seven Language Dictionary - Webster's... (Encyclopaedia Britannica, 1961)
ir, vol1,c.1 ; vol.2,c.1 ; vol.3,c.1/stoc4, jil.1-3,c.1